Microscopic chromosome Xp distal deletions – a challenging issue in prenatal genetic counseling. (25th March 2014) - Sukenik‐Halevy, Rivka; Reches, Adi; Bar‐Shira, Anat; Simchoni, Sharon; Goldstein, Myriam; Orr‐Ortreger, Avi; Yaron, Yuval; Ben‐Shachar, Shay
ABSTRACT Objective A prenatal diagnosis of chromosome X short arm deletions may present a challenge in prenatal genetic counseling. We present clinical and molecular data of carriers of Xp distal deletions. Methods We assessed prenatal and postnatal phenotypes of individuals from three families with large Xp distal deletions and from a fourth family with a small Xp distal deletion. The work‐up included karyotyping, chromosomal microarray analysis, and assessment of the X inactivation pattern. Results Five out of eight women with large deletions had a short stature (<3rd percentile). Subjects from one family had developmental and emotional problems. All female carriers with small deletions had markedly short stature, whereas the men had mildly short stature. Chromosomal microarray analysis revealed 11.7‐19.3 Mb deletions in three families and a small ~1 Mb deletion in the fourth. The pseudoautosomal region 1 of the X chromosome was deleted in two families with large deletions. X inactivation was skewed in all tested cases with large deletions. Conclusion Xp distal deletions are mainly associated with short stature. Skewing of the abnormal X chromosome may attenuate the phenotype in cases with large deletions. We suggest that prenatal evaluation in such cases should include sonographic follow‐up and assessment of the X inactivation pattern. © 2014 John Wiley & Sons, Ltd.